Effects of different orchard tree pruning residues on the yield and nutrient composition of Lentinus edodes - Zhang, Yuanyuan; Li, Quanshun; Duan, Longfei; Ding, Jian; Li, Yue; Wang, Yong; Xu, Hongyan; Qin, Baofu (Frontiers in Nutrition, 2024)
Introduction As the scale of Lentinus edodes cultivation expands, challenges such as substrate shortages and rising production costs in mushroom cultivation have become increasingly prominent. Fruit tree pruning residue has the potential to serve as an alternative substrate, offering a sustainable solution. This study evaluates the feasibility of incorporating various types of fruit tree pruning residues into L. edodes cultivation. Methods Different ratios of Quercus sawdust (QS), Malus pumila pruning (MPP), Vitis vinifera pruning (VVP), Actinidia deliciosa pruning (ADP), Ziziphus jujuba pruning (ZJP), and Morus alba pruning (MAP) were tested as substrates. The effects on yield, amino acid profiles, and protein content of L. edodes fruiting bodies were analyzed. The control substrate comprised 80% QS, and the experimental groups incorporated varying ratios of fruit tree residues. Results Compared with the control, yields increased by 14.86% (QS-MPP), 8.1% (QS-VVP), 18.92% (QS-ZJP), and 22.97% (QS-MAP). The MAP group had 21.21% higher ash content, while the QS-MAP group exhibited the highest crude protein content (10.84% increase). The QS-MPP group showed the highest crude fiber content (1.72 g/100 g). Crude polysaccharide and fat contents in the ZJP group increased by 110.77% and 10.15%, respectively. Mineral content varied, with QS-MPP showing the highest calcium, potassium, manganese, and magnesium levels, and VVP exhibiting the highest iron and copper levels. Amino acid analysis revealed QS-MPP had the highest levels of threonine, valine, isoleucine, serine, cysteine, glycine, and histidine, while QS-VVP had the highest leucine, aspartate, glutamate, and arginine levels. The best formulation was determined as 40% QS, 40% MPP, 17% bran, 1% sucrose, 1% CaCO3, and 1% gypsum. Discussion These results highlight the potential of fruit tree pruning residues as a sustainable substrate for L. edodes cultivation, ensuring high yields and enhanced nutritional quality. This approach can contribute to cost-effective and environmentally friendly mushroomproduction.